Four-Stage Sequential Extraction of Heavy Metals from Zayandeh-Rud River Sediments - TALEBI, S.M.; SEMNANI, A. (Asian Journal of Chemistry, 2010)
The fractionation and release of seven heavy metals e.g., lead, copper, chromium, nickel, manganese, zinc and iron from river sediments under the different conditions was investigated by performing a four-stage sequential extraction. The results showed the potential mobility of heavy metals in river sediments. Considerable amounts of chromium and iron were extracted at 4th stage and indicate lower potential mobility for these two elements. The concentrations of heavy metals extracted with total extraction procedure were compared with those extracted with the sequential extraction procedure and showed that the proposed method is quite capable to remove whole of the elements from river sediments in different stages. The concentration of heavy metals in 10 different points along the river was also studied and showed that as the river pass the city the concentration of heavy metals increased in the sediments.